Prevalence and Predictors of Iron Deficiency Anemia among Children in Saudi Arabia (The International Journal for Scientific Research, 2023)
Introduction: The long-term impact of iron deficiency anemia on female children was significantly reducing physical growth, neurological development and learning performance. There is limited data about the magnitude of iron deficiency anemia in Saudi Arabia in young children. This study aimed to assess the prevalence and determinants of iron deficiency anemia in children attending primary health care at the age of the school entry. Methods: This is a cross-sectional study including children at the age of school entry and they should be tested for detection of anemia after their parents sign an informed consent. Children with other types of anemia were excluded from this study. The minimal sample size is calculated using Raosoft calculator based on the equation for proportion estimation. Based on this proportion, at the confidence level of 95% and estimation error of 0.05 the initial sample size is calculated to be 384 participants. A questionnaire was used to collect data from the mothers or caregiver for the children.Results: A total sample of 384 attendants in PHC centers responded to the questionnaire, of them 59.5% were males. About 68% of the mothers have a high level of education as university or postgraduate studies and 83% were married. The prevalence of anemia was found to be 24% among children for both genders. Only nationality was a significant predictor for iron-deficiency anemia among children. Saudis children had a significantly lower prevalence of anemia than non-Saudis. Conclusions:  The prevalence of anemia among children at age of school entry was high and more attention to the nutritional habits of children should be given by mothers and health specialists. Educational campaign should be conducted to increase awareness about proper children nutrition among women, particularly women with non-Saudi nationality.
Keywords: Iron; Anemia; Children; Mothers; Saudi